Nutrition in the prevention and treatment of disease - Coulston, Ann M.; Boushey, Carol J.; Ferruzzi, Mario G.; Delahanty, Linda M. (Academic Press, 2017)
"Nutrition in the Prevention and Treatment of Disease, Fourth Edition, is a compilation of current knowledge in clinical nutrition and an overview of the rationale and science base of its application to practice in the prevention and treatment of disease. In its fourth edition, this text continues the tradition of incorporating new discoveries and methods related to this important area of research"--Provided by publisher.